Understanding the influence of digital technology on human cognitive functions: A narrative review - Eugénia Correia de Barros (IBRO Neuroscience Reports)
In the era of rapid digitalization, the widespread integration of digital technology into various aspects of daily life has sparked significant interest in understanding its impact on cognitive mental processes. While the emerging data suggests that its influence may be positive or negative, the depth of evidence regarding neurobiological mechanisms remains limited. This review aims to synthesize previously published studies and develop a comprehensive framework that systematically categorizes digital technologies, the cognitive functions they impact, and developmental stages around the concept of neuroplasticity, while clearly illustrating their interconnections. Despite acknowledged limitations, through an exhaustive approach, this paper intends to offer a dynamic perspective on the effects of digital media on the human brain, before the onset of addiction.